4D Reconstruction of Tangible Cultural Heritage Objects from Web-Retrieved Images - Kyriakaki, Georgia; Doulamis, Anastasios; Doulamis, Nikolaos D.; Ioannides, Marinos; Makantasis, Konstantinos; Protopapadakis, Eftichios; Hadjiprocopis, Andreas; Wenzel, Konrad; Fritsch, Dieter; Klein, Michael; Weinlinger, Guenther (My University, 2014)
The number of digital images that are available online today has reached unprecedented levels. Recent statistics showed that by the end of 2013 there were over 250 billion photographs stored in just one of the major social media sites, with a daily average upload of 300 million photos. These photos, apart from documenting personal lives, often relate to experiences in well-known places of cultural interest, throughout several periods of time. Thus from the viewpoint of Cultural Heritage professionals, they constitute valuable and freely available digital cultural content. Advances in the fields of Photogrammetry and Computer Vision have led to significant breakthroughs such as the Structure from Motion algorithm which creates 3D models of objects using their 2D photographs. The existence of powerful and affordable computational machinery enables the reconstruction not only of single structures such as artefacts, but also of entire cities. This paper presents an overview of our methodology for producing cost-effective 4D – i.e. in space and time – models of Cultural Heritage structures such as monuments and artefacts from 2D data (pictures, video) and semantic information, freely available ‘in the wild’, i.e. in Internet repositories and social media. State-of-the-art methods from Computer Vision, Photogrammetry, 3D Reconstruction and Semantic representation are incorporated in an innovative workflow with the main goal to enable historians, architects, archaeologists, urban planners and other cultural heritage professionals to reconstruct cost-effective views of historical structures out of the billions of free images floating around the web and subsequently interact with those reconstructions.
Keywords: 3D Reconstruction; Photogrammetry; Semantic representation